Human Sperm Cryopreservation: Update on Techniques, Effect on DNA Integrity, and Implications for ART - Di Santo, Marlea (Hindawi Publishing Corporation, 2012)
Cryopreservation of human spermatozoa—introduced in the 1960's—has been recognized as an efficient procedure for management of male fertility before therapy for malignant diseases, vasectomy or surgical infertility treatments, to store donor and partner spermatozoa before assisted reproduction treatments and to ensure the recovery of a small number of spermatozoa in severe male factor infertility. Despite the usefulness of it, cryopreservation may lead to deleterious changes of sperm structure and function: while the effects of cryopreservation on cells are well documented, to date there is no agreement in the literature on whether or not cryopreservation affects sperm chromatin integrity or on the use of a unique and functional protocol for the freezing-thawing procedure. Therefore, sperm cryopreservation is an important component of fertility management and much of its successful application seems to affect the reproductive outcome of assisted reproduction technologies (ART): appropriate use of cryoprotectants before and sperm selection technologies after cryopreservation seem to have the greatest impact on preventing DNA fragmentation, thus improving sperm cryosurvival rates.